The pattern of pediatric tuberculosis and treatment outcomes from 2012 to 2016 in Erbil City, Iraq - Mawlood, Ahang Hasan (Zanco Journal of Medical Sciences (ZJMS), 2020)
Background and objective: M. tuberculosis is one of the main causes of morbidity and mortality in many countries and is considered a priority global health problem. Although it is a curable disease, every year about nine million people develop active disease, and two million die from it. This study aimed to find the pattern of tuberculosis among children in Erbil city and determine the treatment outcomes of pediatric tuberculosis. Methods: From March 2012 to March 2016, 142 patients younger than 18 years with confirmed diagnosis of tuberculosis were registered and treated at the Chest and Respiratory Disease Centre in Erbil. The diagnosis of tuberculosis was performed based on routine tests at the center. AFB smear staining, GeneXpert assay, and culture methods when required for further confirmations using L-J media. Results: The total number of the studied records of tuberculosis was 729 during five years (2012-2016). More than half (55.6%) of patients aged ≤ 18 years were males. It is evident that the number of cases is increasing with the progress of years, but the difference was not significant between the years (P = 0.534). The death rate was 9.1% among patients of the whole sample, but no significant association was detected between age and outcome and was highest (22.7%) among patients aged 7-12 years (P = 0.142). Conclusion: Tuberculosis is still a very severe disease with high mortality rates in children. Early recognition of infection associated with correct early treatment, systematic entourage investigation, and chemoprophylaxis by isoniazide in all children under five years of age is essential for attempting to reduce these prognostic indices.